ISOMETRIC EXERCISES AND MASSAGE FOR HYPERTENSIVE PATIENTS AT PROLANIS MEMBERS AT JOHAR BARU HEALTH CENTER, JAKARTA - Prabawati, Dewi; Suprapti, Fitriana; Maxmilla Yoche, Maria; Felicia, Felicia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Hypertension is a global health problem and is recognized as a major contributor to the burden of cardiovascular disease. The prevalence of hypertension continues to increase due to lifestyle changes such as smoking, obesity and psychosocial stress. It is important to educate people with hypertension to self-manage themselves at home. This community service activity aimed to provide health information about hypertension and self-management in the form of exercise and massage. This activity was attended by 30 Prolanis (Chronic Disease Management Program) participants at Johar Baru Health Center in Jakarta. There were 5 sessions in this activity: Session 1&2 for registration and measurement of physiological parameters, followed by cardiovascular exercises. Session 3 for health education about hypertension in general, then followed by next session on isometric exercises with a tennis ball and final session on of self-massage exercise. The evaluation done on this activity showed that the participants demonstrated isometric exercises and back massage techniques that can be carried out independently. Hypertensive patients are expected to be actively involved in Prolanis activities and conduct self-management intervention to maintain their blood pressure and prevent the complications.